Cortisol levels associated with mortality in children with critical illness: a systematic review - Tolibin, Restu Triwulandani; Widiretnani, Septin; Moelyo, Annang Giri (Paediatrica Indonesiana, 2023)
Background Critically ill patients, including those with sepsis, have increased cortisol levels due to activation of the hypothalamic-pituitary-adrenal (HPA) axis or critical illness-related corticosteroid insufficiency (CIRCI). Objective To evaluate for a possible association between cortisol levels and mortality from sepsis in pediatric patients by systematic review of the literature. Methods A systematic review was conducted on studies involving critically ill children, including those with sepsis. We included studies published between 2011-2020 analyzing data on cortisol levels (total serum cortisol, serum-free cortisol, salivary cortisol, real-time free cortisol, basal serum cortisol and post-adrenocorticotropin hormone (ACTH) stimulation test, or basal salivary cortisol and post-ACTH stimulation test), the predictive score for mortality (Pediatric Logistic Organ Dysfunction/PELOD), Pediatric Risk of Mortality (PRISM), Pediatric Index of Mortality (PIM), Vasotropic Inotropic Score (VIS), or Pediatric Critical Illness Score (PCIS)], mortality (non-survivor percentage), and CIRCI percentage as an outcome in patients with critical illness, sepsis, and septic shock. Results Twenty-one observational studies were included in our systematic review, with a total of 2,212 subjects, 916 of whom had sepsis. Nineteen studies indicated a positive association between elevated cortisol levels and mortality in critically ill children, but 2 studies stated that there was no association with the CIRCI percentage of 32.3 and 84.3% respectively. The mortality percentage of critically ill patients with elevated cortisol levels and sepsis were 25.81 (2.7-60)% and 35.31 (6-60)%, respectively. The percentages of CIRCI in critically ill and sepsis patients were 21.91 (0-84.3)% and 21.35 (0-84.3)%, respectively. Conclusion Cortisol levels may increase or decrease in critically ill children. Elevated cortisol levels are associated with mortality in septic children. The effect of CIRCI on mortality in critically ill children cannot be concluded.